The significance of glutathione for photoprotection at contrasting temperatures in the alpine plant species Soldanella alpina and Ranunculus glacialis. - Laureau, Constance; Bligny, Richard; Streb, Peter (Physiologia Plantarum, 2011)
International audience The significance of total glutathione content was investigated in two alpine plant species with highly differing antioxidative scavenging capacity. Leaves of Soldanella alpina and Ranunculus glacialis incubated for 48 h in the presence of buthionine-sulfoximine had 50% lower glutathione contents when compared with leaves incubated in water. The low leaf glutathione content was not compensated for by activation of other components involved in antioxidative protection or electron consumption. However, leaves with normal but not with low glutathione content increased their ascorbate content during high light (HL) treatment (S. alpina) or catalase activity at low temperature (LT) (R. glacialis), suggesting that the mere decline of the leaf glutathione content does not act as a signal to ameliorate antioxidative protection by alternative mechanisms. CO(2)-saturated oxygen evolution was not affected in glutathione-depleted leaves at various temperatures, except at 35°C, thereby increasing the high temperature (HT) sensitivity of both alpine species. Leaves with low and normal glutathione content were similarly resistant to photoinhibition and photodamage during HL treatment at ambient temperature in the presence and absence of paraquat or at LT. However, HL- and HT-induced photoinhibition increased in leaves with low compared to leaves with normal glutathione content, mainly because the recovery after heat inactivation was retarded in glutathione-depleted leaves. Differences in the response of photosystem II (PSII) activity and CO(2)-saturated photosynthesis suggest that PSII is not the primary target during HL inactivation at HT. The results are discussed with respect to the role of antioxidative protection as a safety valve for temperature extremes to which plants are not acclimated.